IMPACT OF ISIS ON RADICAL GROUPS OF SOUTHEAST ASIAN COUNTRIES - Mustafa Selçuk; Nikos Panagiotou (Journal of Islamic World and Politics, 2020)
Radicalization is not a new phenomenon in Southeast Asia. Islamic radicalization increased and became a significant issue in Southeast Asia since 2001. Faith-based organizations that have supported the radical spreading of misinformation, and therefore various measures had many casualties. The development of Islamic radicalism in Southeast Asia is starting to spreading in Indonesia, Philippines and Malaysia. This research focuses on how the ideology of ISIS effected (re-activated) radical groups in Southeast Asia. More specifically through discourse analysis our aim to analyze similarities in discourses and frames through their communication campaigns. In additionally we examined how the spreading of Islamic radicalism in Southeast Asia and broaden the scope of knowledge on the impact of Islamic radicalization in other regional countries.